Solid solution or amorphous phase formation in TiZr-based ternary to quinternary multi-principal-element films - Braic, Mariana; Braic, Viorel; Vladescu, Alina; N. Zoita, Catalin; Balaceanu, Mihai (Progress in natural science, 2014)
TiZr-based multicomponent metallic films composed of 3–5 constituents with almost equal atomic concentrations were prepared by cosputtering of pure metallic targets in an Ar atmosphere.X-ray diffraction was employed to determine phase composition,crystalline structure,lattice parameters,texture and crystallite size of the deposited films.The deposited films exhibited only solid solution(fcc,bcc or hcp) or amorphous phases,no intermetallic components being detected.It was found that the hcp structure was stabilized by the presence of Hf or Y,bcc by Nb or Al and fcc by Cu.For the investigated films,the atomic size difference,mixing enthalpy,mixing entropy,Gibbs free energy of mixing and the electronegativity difference for solid solution and amorphous phases were calculated based on Miedema’s approach of the regular solution model.It was shown that the atomic size difference and the ratio between the Gibbs free energies of mixing of the solid solution and amorphous phases were the most significant parameters controlling the film crystallinity.